ISOCYANATE-FREE AND BPA-FREE CO-POLY(URETHANE-CARBONATE) - Pyo, Sang Hyun ; 0000-0002-5037-2748; Hatti-Kaul, Rajni (World Intellectual Property Organization, 2024)
The invention pertains to a process for preparing a random co-poly(urethane-carbonate) comprising reacting a 6-membered di-cyclic carbonate with a polyamine via a ring- opening polymerization (ROP) by catalytic control for carbonate unit formation, in the presence of a catalyst, through a ring-opening polymerization reaction. Also, the invention pertains to a random co-poly(urethane-carbonate) being obtainable by said process.